Environmental effects on photosynthetic capacity of bean genotypes - Ribeiro, Rafael Vasconcelos; dos Santos, Mauro Guida; Souza, Gustavo Maia; Machado, Eduardo Caruso; de Oliveira, Ricardo Ferraz; Angelocci, Luiz Roberto; Pimentel, Carlos (Pesquisa Agropecuaria Brasileira, 2004)
Photosynthetic responses to daily environmental changes were studied in bean (Phaseolus vulgaris L.) genotypes ‘Carioca’, ‘Ouro Negro’, and Guarumbé. Light response curves of CO2 assimilation and stomatal conductance (gs) were also evaluated under controlled (optimum) environmental condition. Under this condition, CO2 assimilation of ‘Carioca’ was not saturated at 2,000 mol m-2 s-1, whereas Guarumbé and ‘Ouro Negro’ exhibited different levels of light saturation. All genotypes showed dynamic photoinhibition and reversible increase in the minimum chlorophyll fluorescence yield under natural condition, as well as lower photosynthetic capacity when compared with optimum environmental condition. Since differences in gs were not observed between natural and controlled conditions for Guarumbé and ‘Ouro Negro’, the lower photosynthetic capacity of these genotypes under natural condition seems to be caused by high temperature effects on biochemical reactions, as suggested by increased alternative electron sinks. The highest gs values of ‘Carioca’ were observed at controlled condition, providing evidences that reduction of photosynthetic capacity at natural condition was due to low gs in addition to the high temperature effects on the photosynthetic apparatus. ‘Carioca’ exhibited the highest photosynthetic rates under optimum environmental condition, and was more affected by daily changes of air temperature and leaf-to-air vapor pressure difference.